The Influence of Tax Knowledge, Tax Services, and Tax Sanctions on MSME Taxpayer Compliance in Bandung City: - Anna Putri Muslim; Chintya Wijaya Putri; Dani Ikhwan; Eka Nursanti; Faradilla Putri; Asywaq Mudhiah; Nazwa Putri Ramadhani (Universitas Dehasen Bengkulu, 2026)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia remains relatively low, despite various government efforts such as improving tax knowledge, enhancing the quality of tax services, and enforcing tax sanctions. This condition indicates the need for empirical research to identify the factors influencing MSME taxpayer compliance. This study aims to analyze the effects of tax knowledge, tax services, and tax sanctions on MSME taxpayer compliance in Bandung City. The research employs a quantitative method with a survey approach. The sampling technique used is accidental sampling, and data were collected through the distribution of questionnaires both online and offline using Google Forms. The collected data were analyzed using multiple linear regression analysis to examine the influence of more than one independent variable on a single dependent variable. The results show that simultaneously, tax knowledge, tax services, and tax sanctions have a significant effect on MSME taxpayer compliance, explaining approximately ±64.5% of the variation in compliance, while the remaining variance is influenced by other factors outside this study. Partially, tax sanctions as an external factor have a significant effect on MSME taxpayer compliance with a significance value of <0.001. Meanwhile, tax knowledge and tax services as internal factors do not have a significant effect, with significance values of 0.210 and 0.995, respectively. These findings indicate that although MSME taxpayers possess tax knowledge and receive tax services, these factors alone are insufficient to encourage voluntary compliance. Therefore, this study emphasizes the importance of balancing educational approaches with the enforcement of tax sanctions to sustainably improve MSME taxpayer compliance.